THE ORIGINS OF HOMOSEXUALITY - BĂJENESCU, Titu-Marius I. (Journal of Social Sciences)
Homosexuality is defined as a state of sexual attraction to an individual of the same sex. This behaviour does not only concern humans, but also all animal species on earth. But it is interesting to ask whether homosexuality can be limited to this definition? If so, then what about the married man with several children who has never had a homosexual relationship, but secretly spends his time on gay websites? What about this woman who is equally attracted to women and men? These are all questions that call for greater insight. The issue of homosexuality is more complicated than it seems. It is inappropriate to look at sexuality without addressing the fantasies and other urges that surround it.